2015
DOI: 10.1007/s10549-015-3369-4
|View full text |Cite
|
Sign up to set email alerts
|

Family history and risk of pregnancy-associated breast cancer (PABC)

Abstract: The risk of breast cancer is at least two-fold increased in young women with a family history of breast cancer. Pregnancy has a dual effect on breast cancer risk; a short-term increase followed by a long-term protection. We investigated if the risk of breast cancer during and within 10 years following pregnancy is affected by a family history of breast cancer. We followed a cohort of women aged 15-44 years between 1963 and 2009 identified in Swedish population-based registers. Family history was defined as hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 131 publications
(306 reference statements)
2
19
1
Order By: Relevance
“…[14] The interactions between pregnancy and breast cancer are complex and variable, may be increased hormonal levels promote proliferation of existing tumours, [15] 29.8% of our patients presented with pregnancy or lactation-associated breast cancer, all presented with larger tumour size. Risk of breast cancer becomes 2 times in patients with family history of breast cancer, however, for PABC, the risk remains the same as for non PABC tumours according to Johansson et al [16] 11.6% of our patients have a positive family history of first-degree relative.…”
Section: Discussionsupporting
confidence: 48%
“…[14] The interactions between pregnancy and breast cancer are complex and variable, may be increased hormonal levels promote proliferation of existing tumours, [15] 29.8% of our patients presented with pregnancy or lactation-associated breast cancer, all presented with larger tumour size. Risk of breast cancer becomes 2 times in patients with family history of breast cancer, however, for PABC, the risk remains the same as for non PABC tumours according to Johansson et al [16] 11.6% of our patients have a positive family history of first-degree relative.…”
Section: Discussionsupporting
confidence: 48%
“…2,4 Therefore, in our second analysis, we evaluated patients diagnosed with breast cancer 1 to 5 years postpartum (PABC-II). More detailed information, in response to questions on an update questionnaire, was received from 307 patients.…”
Section: Resultsmentioning
confidence: 99%
“…17 Similar to our results, Johansson et al found that there was not an association between family history and breast cancer during or within 2 years of pregnancy and even up to 10 years post-partum. 4 As women diagnosed with breast cancer at younger ages are more likely to have a family history of breast cancer, the absence of an association in those with PABC suggests some other causative factor, possibly hormonal. Until relationships are well understood and characterized, family history should be considered when assessing risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family history as a strong risk factor may increase the possibility of breast cancer in young women by at least two-fold. However, studies fail to show any significant increase in the cancer risk among pregnant women with the family history of breast cancer when compared to women without a family history [31,32]. Similar to the general population the most commonly found subtype of breast cancer during pregnancy is infiltrating ductal carcinoma.…”
Section: Discussionmentioning
confidence: 97%